(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article discusses various aspects of cultural creativity of Ualihanov Ch. He is one of the most prominent personalities of the Kazakh culture. He made a contribution to the development of such areas as geography, history, ethnography. However, Kazakh scientists believe that studying the works of his cultural heritage still not suffi cient. And also Ch.Ualihanov as a phenomenon of Kazakh culture is not studied fully. However, in this article, we are studying most his cultural views. He is not only a cultural phenomenon of the Eastern world; also he is person, who introduced the culture of Central Asia to Europe. In that days people at the court believed that representatives of other nationalities are not able to develop or progress, however, Ch. Ualikhanov said: «We are able to accept European culture completely». Kyrgyz people need to pass as a Russian stage and tatar stage to achieve European civilization. To avoid the need to stop the tatar stage obey only the mullahs and ideas of Islam and instead Tatar schools need to open the Russian school. Chokan believed that the tartars have a negative impact on the development of the Kazakh people, for the development of society need ruler who understands the importance of education. Key words: personality, culture, ethnography, Central Asia, education, civilization.